Erucin, a Natural Isothiocyanate, Prevents Polyglutamine-Induced Toxicity in Caenorhabditis elegans via aak-2/AMPK and daf-16/FOXO Signaling - Balducci, Martina; Pérez, Julia Tortajada; del Río, Cristina Trujillo; Pérez, Mar Collado; Carranza, Andrea del Valle; Gomez Escribano, Ana Pilar; Vázquez-Manrique, Rafael P.; Tarozzi, Andrea (International journal of molecular sciences, 2024)
Several neurodegenerative diseases (NDDs), such as Huntington’s disease, six of the spinocerebellar ataxias, dentatorubral-pallidoluysian atrophy, and spinobulbar muscular atrophy, are caused by abnormally long polyglutamine (polyQ) tracts. Natural compounds capable of alleviating polyQ-induced toxicity are currently of great interest. In this work, we investigated the modulatory effect against polyQ neurotoxic aggregates exerted by erucin (ERN), an isothiocyanate naturally present in its precursor glucoerucin in rocket salad leaves and in its oxidized form, sulforaphane (SFN), in broccoli. Using C. elegans models expressing polyQ in different tissues, we demonstrated that ERN protects against polyQ-induced toxicity and that its action depends on the catalytic subunit of AMP-activated protein kinase (aak-2/AMPKα2) and, downstream in this pathway, on the daf-16/FOXO transcription factor, since nematodes deficient in aak-2/AMPKα2 and daf-16 did not respond to the treatment, respectively. Although triggered by a different source of neurotoxicity than polyQ diseases, i.e., by α-synuclein (α-syn) aggregates, Parkinson’s disease (PD) was also considered in our study. Our results showed that ERN reduces α-syn aggregates and slightly improves the motility of worms. Therefore, further preclinical studies in mouse models of protein aggregation are justified and could provide insights into testing whether ERN could be a potential neuroprotective compound in humans.